2019
DOI: 10.1186/s12871-019-0813-8
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of a patient with limb-girdle muscular dystrophy 2B:CARE-compliant case report and literature review

Abstract: Background Limb-girdle muscular dystrophies (LGMDs) belong to few neuromuscular disorders mainly involving pelvic and shoulder girdle muscles. Also, cardiac or pulmonary complications, increased rhabdomyolysis risk when exposed to volatile anesthetics and succinylcholine may increase anesthesia related risks. However, current reports about the anesthesia management of these patients are limited. Case presentation We described our anesthetic management of a 36 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…In a review of the literature, few reports of elective surgeries were found, the majority of the operations being performed under total intravenous anesthesia (TIVA), and few cases with neuraxial anesthesia supplemented with an intrathecal opioid, already included in other studies. 2 , 3 Two operations were performed under neuraxial anesthesia, included in the review by Cao et al, 2 one laparoscopic cholecystectomy with spinal anesthesia technique and one cesarean section with the CSE technique, which included an intrathecal opioid. They performed neuraxial anesthesia to avoid respiratory complications and the need for intubation, invasive ventilation, and neuromuscular blockade, reducing the risks inherent to patients with myopathies, mainly the potential difficulty of weaning from ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a review of the literature, few reports of elective surgeries were found, the majority of the operations being performed under total intravenous anesthesia (TIVA), and few cases with neuraxial anesthesia supplemented with an intrathecal opioid, already included in other studies. 2 , 3 Two operations were performed under neuraxial anesthesia, included in the review by Cao et al, 2 one laparoscopic cholecystectomy with spinal anesthesia technique and one cesarean section with the CSE technique, which included an intrathecal opioid. They performed neuraxial anesthesia to avoid respiratory complications and the need for intubation, invasive ventilation, and neuromuscular blockade, reducing the risks inherent to patients with myopathies, mainly the potential difficulty of weaning from ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…They performed neuraxial anesthesia to avoid respiratory complications and the need for intubation, invasive ventilation, and neuromuscular blockade, reducing the risks inherent to patients with myopathies, mainly the potential difficulty of weaning from ventilation. 2 In these cases, when neuraxial anesthesia was performed, a local anesthetic (bupivacaine) and intrathecal opioid (fentanyl) were also used, and adequate monitoring in the perioperative period was maintained 3 and in only one case a patient-controlled analgesia device was used in the postoperative period. 2 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations